Singapore Investments in China: Implications from Projects During Early 1980s and During Early 1990s - Rajah V. Komaran (Asian Academy of Management Journal, 1999)
It is well known that foreign investment by the industrialized world are driven by the private sector leveraging its technological, management and marketing skills, and that those by developing countries arise because of geographic proximity, social and economic homogeneity, and cultural familiarity. In the case of Singapore, a unique characteristic is the direct participation by government-related corporations and their affiliates, and persuasion by statutory bodies such as the Economic Develepment Board and Trade Development Board for the corporate sector to venture abroad. Although Singapore is active in the property sector in China and elsewhere, its limited technological resource suggest that its future overseas manufacturing would rest on collaborations involving larger scales of operations and higher technologies from the developed world. in fact, as it is inevitable that host countries will require higher quality foreign investment, it is crucial that these alliances be created to take advantage of Singapore's present business experiences and cultural links in China and other Asian countries.